Patient‐reported quality of life in a randomized placebo‐controlled trial of naltrexone/bupropion for obesity. Issue 5 (29th July 2015) - Kolotkin, R. L.; Chen, S.; Klassen, P.; Gilder, K.; Greenway, F. L.
Summary: Weight loss is associated with improved quality of life in some, but not all, weight loss trials. We evaluated changes at 56 weeks in quality of life, measured by the Impact of Weight on Quality of Life‐Lite (IWQOL‐Lite) questionnaire, in a pooled analysis of patient‐level data from four randomized controlled Phase 3 studies of naltrexone/bupropion (NB32 or Contrave®). The total number of subjects was 3362 (NB32 = 2043; placebo = 1319; mean body mass index = 36.3 kg m 2 ; mean age = 46). Improvements in IWQOL‐Lite Total Score were greater in subjects treated with NB32 (11.9 points [SE 0.3]) vs. placebo (8.2 points [SE 0.3]; P < 0.001), corresponding to weight reductions of 7.0% (SE 0.2) and 2.3% (SE 0.2), respectively. Greater improvements were also observed for NB32 vs. placebo on all five subscale scores of the IWQOL‐Lite. Fifty per cent of NB32‐treated subjects achieved clinically meaningful improvements in IWQOL‐Lite Total Score vs. 32.3% of placebo‐treated subjects (odds ratio, 95% confidence interval; 2.09, 1.79–2.44). Subjects losing the most weight (≥15% of baseline weight) experienced the greatest improvement in IWQOL‐Lite Total Score (19.3 points [SE 0.7] for NB32 and 18.7 points [SE 1.3] for placebo; P = 0.624). Improved quality of life was associated with weight reduction and was achieved in more subjects treated with NB32 than placebo.